Análisis De Estructura Y Dinámica De La Cuenta Corriente Y Su Impacto En La Economía Colombiana Del 2012 Al 2022 (2024)
The present study analyzed the structure and dynamics of current account balances, along with their causes and consequences, and their effect on the Colombian economy during the period 2012- 2022. A quantitative analytical-correlational study was conducted, focused on systematic data collection and rigorous numerical analysis, aiming to examine the relationship between current account balances and Gross Domestic Product (GDP) variation